Fertilization and Colors of Plastic Mulch Affect Biomass and Essential Oil of Sweet-Scented Geranium - Anderson de Carvalho Silva; Arie Fitzgerald Blank; Wallace Melo dos Santos; Paloma Santana Prata; Péricles Barreto Alves; Maria de Fátima Arrigoni-Blank (The Scientific World Journal)
Sweet-scented geranium (Pelargonium graveolens L’Hér), a plant belonging to the Geraniaceae family, has medicinal and aromatic properties and is widely used in the cosmetic, soap, perfume, aromatherapy, and food industries. The aim of this study was to evaluate the influence of fertilization and the use of different colors of plastic mulch on sweet-scented geranium biomass and essential oil. Three colors of plastic mulch (black, white, and silver-colored) and a control without plastic mulch were assessed along with three fertilizers (20,000 L·ha−1 of cattle manure; 1,000 kg·ha−1 of NPK 3-12-6; and 20,000 L·ha−1 of cattle manure + 1,000 kg·ha−1 of NPK 3-12-6 fertilizer) and a control without fertilizer. The absence of a soil cover negatively influenced the agronomical variables, while coverage with plastic mulch was associated with increased biomass. The use of fertilizer had no effect on the evaluated agronomic variables. When cattle manure and NPK 3-12-6 were used together, combined with white or black plastic mulch, the highest yields of essential oil were obtained. For the silver-colored plastic mulch, higher amounts of essential oil (6,9-guaiadien) were obtained with mineral fertilizer.